Resolution-aware Slicing of CAD Data for 3D Printing - Onyeako, Isidore (Université d'Ottawa / University of Ottawa, 2016)
3D printing applications have achieved increased success as an additive manufacturing (AM) process. Micro-structure of mechanical/biological materials present design challenges owing to the resolution of 3D printers and material properties/composition. Biological materials are complex in structure and composition. Efforts have been made by 3D printer manufacturers to provide materials with varying physical, mechanical and chemical properties, to handle simple to complex applications. As 3D printing is finding more medical applications, we expect future uses in areas such as hip replacement - where smoothness of the femoral head is important to reduce friction that can cause a lot of pain to a patient. The issue of print resolution plays a vital role due to staircase effect. In some practical applications where 3D printing is intended to produce replacement parts with joints with movable parts, low resolution printing results in fused joints when the joint clearance is intended to be very small. Various 3D printers are capable of print resolutions of up to 600dpi (dots per inch) as quoted in their datasheets. Although the above quoted level of detail can satisfy the micro-structure needs of a large set of biological/mechanical models under investigation, it is important to include the ability of a 3D slicing application to check that the printer can properly produce the feature with the smallest detail in a model. A way to perform this check would be the physical measurement of printed parts and comparison to expected results. Our work includes a method for using ray casting to detect features in the 3D CAD models whose sizes are below the minimum allowed by the printer resolution. The resolution validation method is tested using a few simple and complex 3D models. Our proposed method serves two purposes: (a) to assist CAD model designers in developing models whose printability is assured. This is achieved by warning or preventing the designer when they are about to perform shape operations that will lead to regions/features with sizes lower than that of the printer resolution; (b) to validate slicing outputs before generation of G-Codes to identify regions/features with sizes lower than the printer resolution.
Keywords: Additive manufacturing; Three dimensional; Two dimensional; Dots per inch; Computer Aided Design; Fused Filament Fabrication; Fused Deposition Model; Electrom Beam Freeform Fabrication; Electron Beam Melting; Magnetic Resonnance Imaging; Computed Tomography; Rapid Prototyping; Three dimensional printing; Layered Manufacturing; Stereolithography; Selective Laser Sintering; Direct Metal Laser Sintering; Acrylonitrile butadiene styrene; Standard Tessellation Language; Initial Graphics Exchange Specification; Wavefront's Object File; Polygon File; Standard Graphics Exchange Format; Scalable vector graphics